2019
DOI: 10.1001/jamaoncol.2019.1747
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Lung Immune Prognostic Index for Patients Treated for Metastatic Non–Small Cell Lung Cancer

Abstract: IMPORTANCE Previous studies have suggested the importance of the baseline derived neutrophil to lymphocyte ratio (dNLR) and lactate dehydrogenase (LDH) level as prognostic markers. The lung immune prognostic index (LIPI) was shown to be associated with progression-free survival (PFS) and overall survival (OS) among patients with metastatic non-small cell lung cancer (mNSCLC) treated with immune checkpoint inhibitors (ICIs) but not cytotoxic chemotherapy (CCT). OBJECTIVE To determine whether the LIPI is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
151
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 10 publications
9
151
1
2
Order By: Relevance
“…37 The combination of inflammatory markers has been shown to be a significant predictive parameter not only for patients who received ICI, but also chemotherapy, in NSCLC. 20 Patients with mCRPC may have a chance to undergo a wide range of treatment sequences, and the combination inflammatory index will be a useful biomarker.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37 The combination of inflammatory markers has been shown to be a significant predictive parameter not only for patients who received ICI, but also chemotherapy, in NSCLC. 20 Patients with mCRPC may have a chance to undergo a wide range of treatment sequences, and the combination inflammatory index will be a useful biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…This study proposed this combined parameter as the lung immune prognostic index (LIPI). In addition, a subsequent study reported that the LIPI is also a valuable biomarker for predicting prognosis in patients receiving chemotherapy, not only ICIs 20 . There is a variety of treatment options in the advanced stages of PCa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of melanoma patients, we could evaluate the potential interaction between test classifications and NLR [23]-a biomarker of systemic inflammation that has previously shown association with outcomes on ICIs [24,25]. The Kaplan-Meier plots suggested that the difference in outcomes between BDX008 classifications may be qualitatively different in the subgroups defined by NLR: it appeared that patients with NLR <5 classified as BDX008+ had especially good outcomes on anti-PD-1 treatment; while at the same time patients classified as BDX008-had poor prognosis independently of NLR status [46] (Figure 2).…”
Section: Independence Of Proteomic Tests From Clinical Characteristicmentioning
confidence: 99%
“…To date, cell-based surrogate markers for systemic inflammation, such as a neutrophil-to-lymphocyte ratio (NLR) measured in circulation, are most studied and have shown significant prognostic value in cancer [23,24]. An index combining the derived neutrophil/leukocyte-lymphocyte ratio (dNLR) with lactate dehydrogenase (LDH) levels demonstrated strong prognostic potential in NSCLC in different clinical modalities, including immune checkpoint inhibitors [25]. Nonetheless, the predictive potential of these measurements for ICIs relative to other therapies has not been established.…”
Section: Introductionmentioning
confidence: 99%